Speech Acts in EFL Context: A Literature Review - Sulastri, Fera; Saptiany, Shella Gherina (Universitas Siliwangi, 2023)
As a part of crucial skills of communicative competence, there have been enormous studies discussing speech acts. This study aimed at investigating speech acts as interlanguage pragmatics focusing on EFL context. Two main questions addressing on (1) how speech acts availability in text-book used by EFL learners, (2) the frequency of speech acts occurring in the EFL classroom context. By reviewing 20 journals from various reliable sources thematically, it is found that speech act availability in the textbooks exists with an unbalanced proportion of speech act types. In addition, the books provide fewer various strategies of speech acts. Concerning the frequency of speech acts in the EFL classroom, directives are mostly used by the teacher while students tend to use various kinds of speech acts. Further study suggested digging into more contextual settings. Keywords: Speech Acts, EFL, Text-Books